Modification of preparing the blood diluting solution method and studying the blood cell counts of some Syrian Reptiles and Amphibians using the modified method - Mhanna, Hassan Nabih; Ibrahim, Nahla; Al-Masri, Aroub (Journal of natural sciences, life and applied sciences, 2022)
The study aimed to test the validity of the results of the modified blood diluted solution by Natt-Herrick method in order to study the complete blood count of different blood cells in two species of amphibians (Pseudepidalea viridis, Hyla savignyi) in addition to five species of reptiles (Testudo graeca, Chamaeleo chamaeleon recticrista, Ophisops elegans, Lacerta media, Phoenicolacerta laevis) by replacing methyl violet 2B dye included in its composition with methyl violet 10B , where our results were compared with the values ​​of previous studies, there is no any significant differences between the modifying methods compare with the others references using the original methods as the results were within or close to normal limits, and thus this method can be approved.According to the values obtained in this paper, the highest number of red and white blood cells was in L. media, the lowest number of red blood cells was in T. graeca, and the lowest number of white blood cells was in O. elegans.